cfDNA as a surrogate marker for COVID-19 severity in patients with influenza-like symptoms with and without SARS-CoV-2 infections in general practice: a study protocol for a prospective cohort study - Dorothea Dehnen; Elmo Neuberger; Jürgen in der Schmitten; Ekaterini Giagkou; Perikles Simon; Suzan Botzenhardt (BMJ Open)
Introduction The clinical course of patients with a SARS-CoV-2 (COVID-19) infection varies widely, from symptom-free to severe courses that can lead to death. Laboratory values of SARS-CoV-2 patients such as lymphocyte counts or C-reactive protein (CRP) do not allow a prediction of the actual course of the disease. To identify a possible predictive marker for the differentiation and prognosis of illness with influenza-like symptoms with and without SARS-CoV-2 infections in general practice, we will analyse the concentrations of cell-free DNA (cfDNA) levels, laboratory and clinical parameters, temperature, oxygen saturation, breathing rate and concomitant symptoms in patients with flu-like symptoms with and without a SARS-CoV-2 infection.Methods and analysis This is a single-centre, two-arm, parallel longitudinal cohort study with a total of 44 patients. 22 patients with flu-like symptoms without a SARS-CoV-2 infection and 22 patients with flu-like symptoms with a SARS-CoV-2 infection will be recruited. The primary objective is to compare cfDNA levels in ambulatory patients in general practice with flu-like symptoms with SARS-CoV-2 infection with those with influenza like symptoms without a SARS-CoV-2 infection during the disease (day 7 and day 14). The secondary objective is to determine whether there is a correlation between cfDNA concentrations on the one hand, and laboratory and clinical parameters on the other hand. cfDNA, differential blood count, high-sensitive CRP and erythrocyte sedimentation rate will be measured in blood samples, concomitant symptoms will be surveyed via a self-assessment questionnaire, and oxygen saturation, breathing rate and examination of the lungs will be reported by treating physicians.Ethics and dissemination Ethical approval was issued on 1 March 2021 by the Ethics Committee Essen under the number 21-9916-BO. Findings will be published in peer-reviewed open-access journals and presented at national and international conferences.Trial registration number DRKS00024722.